Digital Adaptation Model of Batik SMEs in Responding to Changes in Consumer Behavior in the Society 5.0 Era - Muhammad Abdillah (Program Studi Bisnis Digital Fakultas EKonomi dan Bisnis Universitas PGRI Jombang, 2026)
The rapid advancement of digital technology in the Society 5.0 era has significantly transformed consumer behavior, particularly in information searching, purchasing decisions, and digital interactions, compelling Batik Small and Medium Enterprises (SMEs) to adapt their business practices. This study aims to develop a digital adaptation model for Batik SMEs in responding to changing consumer behavior and maintaining business competitiveness in the digital economy. A qualitative research approach was employed using a multiple case study design involving Batik SMEs in Indonesia. Data were collected through in-depth interviews, observations, and document analysis, and subsequently analyzed using thematic analysis. The findings reveal that the digital adaptation of Batik SMEs is driven by four key dimensions: digital capability development, utilization of digital marketing platforms, innovation in customer engagement strategies, and strengthening of organizational learning. These dimensions contribute to improved market reach, customer responsiveness, and business resilience. The study concludes that successful digital adaptation requires an integrated strategy that combines technological adoption, managerial innovation, and continuous learning. Practically, the proposed model can serve as a strategic reference for Batik SMEs, policymakers, and business development institutions in accelerating digital transformation and enhancing competitiveness in the Society 5.0 era.